Photochemistry and the role of light during the submerged photosynthesis of zinc oxide nanorods - Lihua Zhang (Nature Portfolio, 2018)
Abstract Recently, metal oxide nanocrystallites have been synthesized through a new pathway, i.e., the submerged photosynthesis of crystallites (SPSC), and flower-like ZnO nanostructures have been successfully fabricated via this method. However, the photochemical reactions involved in the SPSC process and especially the role of light are still unclear. In the present work, we discuss the reaction mechanism for SPSC-fabricated ZnO nanostructures in detail and clarify the role of light in SPSC. The results show that both photoinduced reactions and hydrothermal reactions are involved in the SPSC process. The former produces OH radicals, which is the main source of OH − at the ZnO crystal tips, whereas the latter generates ZnO. Although ZnO nanocrystals can be obtained under both UV irradiation and dark conditions with the addition of thermal energy, light promotes ZnO growth and lowers the water pH to neutral, whereas thermal energy promotes ZnO corrosion and increases the water pH under dark conditions. The study concludes that the role of light in the submerged photosynthesis of crystallites process is to enhance ZnO apical growth at relatively lower temperature by preventing the pH of water from increasing, revealing the environmentally benign characteristics of the present process.